2020
DOI: 10.1113/jp279009
|View full text |Cite
|
Sign up to set email alerts
|

Multiple acid‐base and electrolyte disturbances upregulate NBCn1, NBCn2, IRBIT and L‐IRBIT in the mTAL

Abstract: Key points The roles of the Na+/HCO3– cotransporters NBCn1 and NBCn2 as well as their activators IRBIT and L‐IRBIT in the regulation of the mTAL transport of NH4+, HCO3–, and NaCl are investigated. Dietary challenges of NH4Cl, NaHCO3 or NaCl all increase the abundance of NBCn1 and NBCn2 in the outer medulla. The three challenges generally produce parallel increases in the abundance of IRBIT and L‐IRBIT in the outer medulla. Both IRBIT and L‐IRBIT powerfully stimulate the activities of the mTAL isoforms of NBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 68 publications
1
20
0
Order By: Relevance
“…IRBIT was originally identified as a binding partner that inhibits the activity of inositol 1,4,5-trisphosphate receptor (IP3R), a Ca 2+ channel expressed in the endoplasmic reticulum membrane (Ando et al 2003(Ando et al , 2006. IRBIT can stimulate a series of acid-base transporters, such as Na + /HCO 3 − cotransporter NBCe1 (Shirakabe et al 2006), NBCn1 (Hong et al 2013;Wang et al 2020a), NBCn2 (Wang et al 2020a), Na + /H + exchanger NHE3 (He et al 2008;He et al 2010), Cl − /HCO 3 − exchanger SLC26A6 (Park et al 2013), Na + /dicarboxylate cotransporter SLC13A3 (Khamaysi et al 2019). IRBIT can also regulate the calcium calmodulin-dependent kinase II alpha (Kawaai et al 2015), ribonucleotide reductase involved in regulation of DNA synthesis (Arnaoutov & Dasso, 2014), the cleavage and polyadenylation specificity factor involved in RNA splicing (Kiefer et al 2009), and apoptosis regulator Bcl-2 (Bonneau et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…IRBIT was originally identified as a binding partner that inhibits the activity of inositol 1,4,5-trisphosphate receptor (IP3R), a Ca 2+ channel expressed in the endoplasmic reticulum membrane (Ando et al 2003(Ando et al , 2006. IRBIT can stimulate a series of acid-base transporters, such as Na + /HCO 3 − cotransporter NBCe1 (Shirakabe et al 2006), NBCn1 (Hong et al 2013;Wang et al 2020a), NBCn2 (Wang et al 2020a), Na + /H + exchanger NHE3 (He et al 2008;He et al 2010), Cl − /HCO 3 − exchanger SLC26A6 (Park et al 2013), Na + /dicarboxylate cotransporter SLC13A3 (Khamaysi et al 2019). IRBIT can also regulate the calcium calmodulin-dependent kinase II alpha (Kawaai et al 2015), ribonucleotide reductase involved in regulation of DNA synthesis (Arnaoutov & Dasso, 2014), the cleavage and polyadenylation specificity factor involved in RNA splicing (Kiefer et al 2009), and apoptosis regulator Bcl-2 (Bonneau et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to PTs, where NBCe1-A exports Na + and CO 3 2− across the BLM, here in the TAL, AE2 exchanges cytosolic HCO 3 − for Cl − at the BLM. In addition to AE2, investigators have identified NBCn1 and (in rat) NBCn2 in the BLM of the TAL [ 131 , 151 , 152 , 153 ]. Because NBCn1 and NBCn2 normally operate in an inward direction [ 154 ], it seems unlikely that they contribute to HCO 3 − reabsorption per se.…”
Section: Carbonic Anhydrases Along the Nephronmentioning
confidence: 99%
“…The responses of different regions of the kidney to hypoxia also differ. The medullary thick ascending limbs (mTALs) play a central role in maintaining systemic acid-base and electrolyte homeostasis ( 150 ). The mTALs and straight segment of the proximal tubule have a strong demand for extramedullary oxygen transport from the renal tubules, which are very vulnerable to hypoxia ( 22 ).…”
Section: Metabolic Reprogramming and Hypoxia In Renal Fibrosismentioning
confidence: 99%